INFLUENCE TRAINING WORK AND DEVELOPMENT SOURCE POWER HUMAN RESPONSE TOWARDS EMPLOYEE PERFORMANCE - Cindi Wulandari Bakri; Saharuddin Saharuddin; Samsinar Samsinar (LPPM STIE Muhammadiah Bandung, 2025)
This research has the aim to analyze how job training and human resource development influence employee performance at BRI Bank, Palopo Branch. The method used is a survey, with data collection through a questionnaire distributed via Google Form and using a Likert scale. All employees in the research population were sampled. The results of this study indicate that job training individually does not have a significant effect on employee performance, whereas human resource development has a significant influence. Furthermore, when both variables job training and human resource development are combined, they have a significant impact on employee performance. These findings provide deeper insights for the management of BRI Bank, Palopo Branch, regarding the importance of human resource development in improving employee performance. The study also highlights the need to evaluate and enhance the effectiveness of existing training programs. Additionally, it is recommended that management pay attention to other factors that may strengthen training outcomes, such as organizational culture and work environment, to further optimize human resource quality and overall performance.